ASPECTS OF THE STOCK VALUATION AND ACCOUNTING IN AGRICULTURAL UNITS IN ROMANIA - Mariana BANUTA; Marilena–Ionica RADULICA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper approaches a current and common and topical problem of the business entities operating in agriculture, the stock valuation and accounting problem. Thus, gradually the article starts from the delimitation of the categories of inventories in agriculture, continues with the reasons for the need to valuate them and shows the stock valuation methods in the current accounting and in other specific situations.